A Method for Space Safety Wall Analysis and Regression Trajectory Planning of Cable-driven Parallel Rehabilitation Robot - Xiang Li; Weida Li; Juan Li; Hongmiao Zhang; Hong Gu (Jixie chuandong)
During gait rehabilitation training， patients with hemiplegia or stroke are prone to muscle cramps， which can cause them to lose their balance due to their inability to support their weight and cause secondary injuries. In response to the above problems， a six-degree-of-freedom parallel rehabilitation robot driven by eight cables is designed， which can not only perform gait training on patients but also implement effective anti-fall protection for patients. Firstly， the configuration of the robot is described， and its kinematics model is established by using the closed vector quadrilateral method. Secondly， combined with the characteristics of cable-driven， a concept of a robot force control workspace and its solution method are proposed based on the statics analysis. In order to avoid secondary injuries to patients after losing their balance， a space trajectory safety wall is further proposed based on the force-controlled working space， which classified the possible shapes to be protected for patients and studied the space trajectory path planning method for their return to the safety wall. Finally， two different types of to-be-protected profiles are selected to study the changes in cable length and tension as they moved along the regression trajectory which verified the effectiveness and rationality of the trajectory planning method for the return safety wall.